Effectiveness of grid analogy for bridge deck analysis - Cheong, Tang Chi (2000)
Bridge decks have traditionally been designed using a simplified model known as the Grillage Analogy Method. Grillage Analogy Method shows how complex structures can be analyzed with physical reasoning and relatively simple computer models, and without complicated mathematics. In recent years the computer methods of grillage has become very popular and accessible as microcomputers and software have developed rapidly. Bridge deck analysis provides bridge designers with the knowledge to understand the behaviour of bridge decks, to be familiar with and to understand the various numerical modeling techniques and to know which technique is best suited to each bridge type. This study focuses on the analysis of the bridge deck using Grillage Analogy Method and Finite Element Method, identifying the effectiveness of Grillage Analogy Method for bridge deck analysis. Tasks being addressed by this case study are the analysis for various types of bridge deck structures which included right angle solid slab deck, skew angle solid slab deck, right angle T-beam bridge deck with 2 end diaphragms, right angle T 8beam bridge deck with 5 diaphragms, skew angle T -beam bridge deck with 2 end diaphragms, curved solid slab deck, single box girder and voided slab deck. The structural details for each bridge deck are further illustrated in each chapter. This study provided information structures that show the percentage differences of the Grillage Analogy Method compared to Finite Element Method in bridge deck analysis using LUSAS Finite Element Software.